PERENCANAAN JALUR INTERPRETASI PENDAKIAN KAWAH RATU TAMAN NASIONAL GUNUNG HALIMUN SALAK - Hasibuan, Ratna Sari (Universitas Nusa Bangsa, 2017)
Kawah Ratu is one of the tourist attractions in the highlands of the Mount Salak Forest, Mount Halimun Salak National Park, Pasir Reungit Village, Bogor. Existing tourism activities can have a positive and negative impact on the surrounding environment. To reduce the negative impact that was usually caused by visitors, it takes activities that can balance the activities of traveling and protecting the environment, namely the interpretation of nature. The purpose of this research was to identify the existing Kawah Ratu climbing trail to be developed as an interpretation trail and to make an interpretation program for the Kawah Ratu hiking trail. The research method was descriptive analysis, by analyzing primary data using Quantum 2.1 software and overlaying with Mount Bunder maps taken from Google earth to produced interpretation trail. The results of the Interpretation trail of the Kawah Ratu trail were Pine and Rasamala Forests, Medicinal Plants, Mushroom Habitats, Flowering Plants, Orchid Plants, Cangkuang Plants, Cigamea and Amphibious Rivers, Fern Plants, Mountain Forests (Montana) and Kawah Ratu. The trail of interpretation of the Kawah Ratu climb that was made has a length of about 3.7 Km with a normal travel time of around Â± 1 hour 20 minutes of travel. Some alternative interpretation programs compiled were one-day travel packages, Frog and Toad Kawah Ratu, and Metallic Battle on wide screen.Â Keywords:Mount Halimun Salak National Park, interpretation trail, interpretation pragramme